A homolog of the mammalian GTPase Rab2 is present in Arabidopsis and is expressed predominantly in pollen grains and seedlings. - Moore, I; Diefenthal, T; Zarsky, V; Schell, J; Palme, K (1997)
Vesicle traffic between the endoplasmic reticulum and the Golgi apparatus in mammals requires the small GTP-binding protein Rab2, but Saccharomyces cerevisiae appears not to have a Rab2 homolog. Here it is shown that the higher plant, Arabidopsis thaliana, contains a gene, At-RAB2, whose predicted product shares 79% identity with human Rab2 protein. Transgenic plants containing fusions between beta-glucuronidase and sequences upstream of At-RAB2 demonstrated histochemical staining predominantly in maturing pollen and rapidly growing organs of germinating seedlings. beta-glucuronidase activity in pollen is first detectable at microspore mitosis and increases thereafter. In this respect, the promoter of At-RAB2 behaves like those of class II pollen-specific genes, whose products are often required after germination for pollen tube growth. Seedling germination and pollen tube growth are notable for their unusually high rates of cell wall and membrane biosynthesis. These results are consistent with a role for At-RAB2 in secretory activity.